In vitro culture of parasitic stages of Haemonchus contortus - Niciura, Simone Cristina Méo; Minho, Alessandro Pelegrine; McIntyre, Jennifer; Benavides, Magda Vieira; Okino, Cintia Hiromi; Esteves, Sergio Novita; Chagas, Ana Carolina de Souza; Do Amarante, Alessandro Francisco Talamini [UNESP] (FapUNIFESP (SciELO), 2023)
Haemonchus contortus is a constraint to sheep production. Seeking to reduce the use of hosts and produce parasitic stages in large-scale, a 42-day in vitro culture protocol of H. contortus third-stage larvae was optimized using Dulbecco’s modified Eagle’s medium (DMEM). In cell-free culture, larvae were maintained at 39.6°C, in acidic media (pH 6.1) for 3 or 6 days with Δ4-dafachronic acid followed by DMEM pH 7.4 supplemented or not with Fildes’ reagent. In DMEM pH 7.4 at 37°C, supplementation with Caco-2 cells was compared to Fildes. On Day 14, fourth-stage larvae (L4) development rates in acidic media supplemented (86.8–88.4%) or not (74.4–77.8%) with Fildes and in Caco-2 cell co-culture (92.6%) were similar, and superior to DMEM pH 7.4 with Fildes (0.0%). On Day 21, Caco-2 cell co-culture resulted in higher larvae differentiation (25.0%) and lower degeneration (13.9%) compared to acidic media (1.5–8.1% and 48.6–69.9%, respectively). This is the first report of prolonged in vitro culture of H. contortus larvae using commercial media in co-culture with Caco-2 cells. Although no progression to the adult stage, Caco-2 cell co-culture resulted in morphological differentiation of H. contortus L4 and larval viability for up to 28 days.
Cultivo in vitro de estádios parasitários de Haemonchus contortus
Keywords: Fourth-stage larvae; gastrointestinal nematodes; prolonged in vitro culture; replacement of in vivo methods; sheep